Challenges and opportunities in hydroxyurea access and adherence for sickle cell disease patients at Komfo Anokye Teaching Hospital: Insights from healthcare providers - Josephine Mensah; Afia Frimpomaa Asare Marfo; Mercy Naa Aduele Opare-Addo; Paul Obeng; Amos Amoako-Adusei; Karl Osei Afoduo; Bright Ansah Adjei; Pauline Boachie Ansah; Kwame Ohene Buabeng (PLoS ONE, 2026)
Hydroxyurea is a vital medication for managing Sickle cell disease, yet access and adherence remain significant challenges in low-resource settings. This qualitative study explored challenges and opportunities in hydroxyurea access and adherence among Sickle cell disease patients at the Komfo Anokye Teaching Hospital in Ghana. Alongside, the utility of the Ahodwo CommCare mobile App in enhancing Sickle cell disease management was explored. Semi-structured interviews were conducted with six healthcare providers, including doctors, nurses, and pharmacists from May 12 to August 15, 2022. This study found that the key barriers to hydroxyurea access and adherence include financial constraints, medication stock-outs, administrative inefficiencies, bureaucratic delays, patient-related factors such as forgetfulness and concerns about side effects, and practical challenges in administering the medication especially to children. The healthcare workers indicated that reconstituting the medication into suspension added both cost and time constraints to children who cannot take capsules hence affecting access to hydroxyurea. Facilitators to access and adherence identified included patient education, streamlined procurement processes, and government support for medication subsidies. This study found that patient education sessions should emphasize the benefits of hydroxyurea treatment and the importance of adherence to prescribed regimens. The study also revealed limited awareness and utilization of the Ahodwo CommCare app among healthcare personnel, highlighting the need for targeted training and integration into clinical workflows. These findings underscore the importance of multifaceted interventions involving healthcare workers, hospital management, and government stakeholders to improve hydroxyurea access and adherence, ultimately enhancing Sickle cell disease patient outcomes.